CFD analysis of the flow in the near wake of a generic PWR mixing grid. (August 2015) - Bieder, Ulrich; Falk, François; Fauchet, Gauthier
Highlights: The flow in a 5 × 5 rod bundle with mixing grid is analyzed experimentally and with CFD. LES and RANS (k–ε) calculations are performed. The parallelism of the Trio_U code was tested with a strong scaling method. Close downstream of the grid, k–ε and LES give similar results and fit well the experiment. Abstract: The flow in fuel assemblies of PWRs with mixing grids has been analyzed with CFD calculations by numerous authors. The comparison between calculation and experiment has often shown an insensitivity of the calculated cross flow velocity on the turbulence modeling. The study presented here was carried out to confirm this result. The comparison between measurements in the AGATE facility (5 × 5 tube bundle) and Trio_U calculations with a linear eddy viscosity turbulence model (k–ε) and Large Eddy Simulations (LES) is presented. The AGATE experiments have originally not been designed for CFD validation but to characterize different types of mixing grids. Nevertheless, the quality of the experimental data allows the quantitative comparison between measurement and calculation. The test section of the AGATE facility has been discretized for the LES calculation on 300 million control volumes by using a staggered grid approach on tetrahedral meshes. 20 days of CPU on 4600 cores of the HPC machine CURIE of the TGCC was necessary to calculate the statistics of the turbulent flow, in particular the mean velocity and the RMS of the turbulent fluctuations. The parallelism of Trio_U was tested up to 10, 000 processor cores using strong scaling and has shown a good efficiency up to about 6000 cores, i.e., 40, 000 control volumes per core. For various distances from the mixing grid, calculated horizontal profiles of the cross flow velocity and of the axial velocity are compared to measurements. It seems that the flow patterns directly downstream of the grid are insensitive to the used turbulence model. Inertia forces related to the geometry of the mixing vanes are dominant in this region. Thus, the application of turbulence models should not be tested close to mixing grids.